International Problems in the Information Policy of Russian Digital Media - Nagovitsina, Tatyana Anatolievna; Gazizov, Ramis Rassyhovich (International Journal of Criminology and Sociology, 2022)
The article is devoted to the study of international issues in leading digital media in Russia. This topic has been and remains a priority on the media agenda of the country. Given the increasing globalization and increasing international factors, the mass audience needs timely and accessible information in this area. When analyzing the materials, attention was paid to the problems, substantive characteristics, structural organization, genre specifics, linguistic and stylistic aspects, which, interacting, form a diverse panorama of international information covered by publications. The information policy of such publications as Lenta.ru, Meduza, Vzglyad and White Square Journal is investigated.